Perspectives on economics and management: Essays in honour of anindya sen - Ghosh, Saibal; Ray, Partha (London Routledge, 2025)
The world of economics and management is being reshaped in more ways than one including rapid advancements in technology and business practices. This book weaves together a diverse set of issues such as consumption patterns, wealth disparities and the management, behaviour and financial health of businesses and consumers to analyse the effectiveness of economic and business strategies. Rapid technological advancements along with the need for cost-effectiveness and convenience are making service providers embrace technology as a partner rather than a tool in their economic journey.